2015
DOI: 10.1111/jfpp.12677
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Color Analysis of Lentils and Rice for Instant Meal Using Image Processing Techniques

Abstract: Typical approaches for measuring color and texture properties are mostly timeconsuming. An image-based method was used to evaluate texture and color in lentils and rice subjected to freeze-drying for an instant meal. Cooked and cooked freeze-dried rehydrated lentils and rice were analyzed by scanning electron microscopy. Texture properties were analyzed by texture analyzer and image analysis. Color was performed with a digital camera. Significant differences for color and texture (P < 0.05) were observed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The GLCM shows the probability that a pixel of a particular grey level occurs at a specified direction and distance ( d =1) from its neighbouring pixels. Grey level co-occurrence matrix is represented by Pd, θ ( i , j ) where counts the neighbouring pair pixels with grey values i and j at the distance of d and the direction of θ (16) (Pieniazek and Messina., 2016b; Pieniazek et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The GLCM shows the probability that a pixel of a particular grey level occurs at a specified direction and distance ( d =1) from its neighbouring pixels. Grey level co-occurrence matrix is represented by Pd, θ ( i , j ) where counts the neighbouring pair pixels with grey values i and j at the distance of d and the direction of θ (16) (Pieniazek and Messina., 2016b; Pieniazek et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Both cooking time and temperature did not significantly impact on L *, a * and b * in WRF, LARF and HARF from cooked grain. Pieniazek et al () reported that higher temperature in the cooking process could decrease the L * values of rice and lentil. Cooking generally reduced L * and b * as a function of cooking time but had no effect on a * value.…”
Section: Resultsmentioning
confidence: 99%
“…The color of the jackfruit seeds was analyzed with a Chroma Meter (CR-300; Minolta, Tokyo, Japan) using the Hunter system, which identifies color using three attributes: L* or lightness (white = 100, black = 0), a (red = positive, green = negative) and b (yellow = positive, blue = negative). The color difference (ΔE), measures the distance in color space between two colors [16] and was determined by comparison to a standard white tile with colorimeter values of L* = 94.5, a = −1.0, and b = 0.2 using ( 12):…”
Section: B) Colormentioning
confidence: 99%